Validation and evaluation of visual acuity and contrast sensitivity with a new digital device: OPTOTAB - Ponce‐García, Víctor; Silva‐Viguera, María‐Carmen; García‐Romera, Marta‐C.; Guerra‐Sancho, Yael; Heredia‐Ríos, Noelia; Bautista‐Llamas, María‐José (Ophthalmic & physiological optics, 2025)
Purpose To validate a new digital device: Optotab®+ (SmarThings4Vision) for measuring visual acuity (VA) and contrast sensitivity (CS). Methods A validation study was conducted involving 20 healthy subjects (aged: 18–29 years). Distance and near VA and CS were assessed using the Optotab®+ and compared with the ETDRS test and Sloan letters for distance VA, the ETDRS test and LEA numbers® near vision card for near VA and the Regan and CSV‐1000 tests for CS. Results No significant differences were noted between the right eye (RE) and left eye (L for distance (p > 0.99) and near VA (p = 0.32) or test–retest measurements (p > 0.05) using the Optotab®+. Distance VA differed significantly from the ETDRS (mean differences: −0.07 and −0.07 logMAR for the RE and LE, respectively, p = 0.01). Intraclass correlation coefficients (ICC) indicated moderate reliability (RE: 0.64, LE: 0.48), while the ANOVA showed no significant differences (p = 0.75 for RE and p = 0.58 for LE). For CS, no significant differences were found between the RE and LE, except at 12 cpd (p = 0.04). ICC was highest at 18 cpd (0.90). A significant test–retest difference was observed at 6 cpd for the RE (0.10 log units, p = 0.01). Comparisons showed significant differences at 6 cpd between Optotab®+ and the CSV‐1000, and at 3, 12 and 18 cpd between Optotab®+ and the Regan test. ICC indicated low to high reliability across spatial frequencies, while the ANOVA did not show significant differences or low variability. No significant inter‐examiner differences were identified in VA and CS (p > 0.05), confirming strong reproducibility. Conclusions This study demonstrates that the Optotab®+ has moderate reliability for VA assessment and higher precision at higher spatial frequencies for CS, suggesting its clinical utility. Outcomes regarding reliability, repeatability and reproducibility support its validity as an effective tool for measuring visual parameters in clinical practice.